(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
ABSTRAC This study aims to determine and analyze the implementation of the law against the crime act of theft with violence and the judge`s considerations in making a decision against the crime act of theft with violence. This research uses a normative research method with a statutory approach and a case approach and uses primary and secondary legal materials. The results of this study show that the panel of judges has sentenced the defendant to two years and six months in prison. The verdict is too light because the criminal threats contained in 365 KUHP are at least threatened with imprisonment for 9; Based on the facts revealed at the trial that the defendant was proven to have committed theft with violence in accordance with 365 (1), (2), 2 KUHP. Likewise, it is in accordance with the formil criminal law article 184 which is applied by the judge. In making a decision, it should not be too light. The criminal threat as stated in 365 KUHP is at least threatened with imprisonment for 9 years in paragraph (1), if it fulfills the elements in aggravating circumstances in paragraph (2), the penalty is 12 years in prison. The panel of judges should consider that the punishment given is not only to provide a deterrent effect for perpetrators of the crime of theft, but also to prevent perpetrators who have the potential to commit the crime of theft. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis pelaksanaan hukum terhadap tindak pidana pencurian dengan kekerasan dan pertimbangan hakim dalam menjatuhkan putusan terhadap tindak pidana pencurian dengan kekerasan. Penelitian ini menggunakan metode penelitian normatif dengan pendekatan perundang-undangan dan pendekatan kasus serta menggunakan bahan hukum primer dan sekunder. Hasil penelitian ini menunjukkan bahwa majelis hakim memutuskan pidana penjara kepada terdakwa selama 2 tahun 6 bulan. Putusan tersebut terlalu ringan dikarenakan ancaman pidana yang tertuang pada pasal 365 KUHP paling sedikit diancam dengan pidana penjara selama 9; Berdasarkan pada faktafakta yang terungkap dipersidangan bahwa terdakwa terbukti telah melakukan pencurian dengan kekerasan sesuai pasal 365 ayat (1),(2), ke-2 KUHP. Begitu pula sudah sesuai dengan hukum pidana formil pasal 184 yang diterapkan oleh hakim. Dalam menjatuhkan putusan hendaknya tidak terlalu ringan. Ancaman pidana yang tertuang pada pasal 365 paling sedikit diancam dengan pidana penjara selama 9 tahun pada ayat (1), jika memenuhi unsur-unsur dalam keadaan memberatkan pada ayat (2) maka ancaman pidananya yaitu 12 tahun penjara. Majelis hakim baiknya mempertimbangkan bahwa pidana yang di berikan bukan hanya untuk memberikan efek jera bagi pelaku tindak pidana pencurian, tapi juga untuk mencegah pelaku yang berpotensi melakukan tindak pidana pencurian